2001
DOI: 10.1063/1.1355357
|View full text |Cite
|
Sign up to set email alerts
|

Domain wall structure in Permalloy films with decreasing thickness at the Bloch to Néel transition

Abstract: Articles you may be interested inPhotoemission electron microscopy study of remanent magnetic domain states in ferromagnetic wedge films deposited on substrates with micrometer-sized square plateaus J. Appl. Phys. 99, 063904 (2006); 10.1063/1.2174119 Variation of domain-wall structures and magnetization ripple spectra in permalloy films with controlled uniaxial anisotropy J. Appl. Phys. 98, 053905 (2005); 10.1063/1.2033152 Magnetic domain wall transitions based on chirality change and vortex position in thin P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 4 publications
3
35
0
1
Order By: Relevance
“…We believe this anomaly can largely be attributed to the nature of the microstructure as the films transition from discrete to coalesced grain structures and a possible accompanying transition in domain dynamics. Trunk and co-authors [37] have shown that a transition from Bloch to Neel domain wall structures takes place with decreasing Py film thickness. Neel wall dynamics were found to govern under conditions where demagnetization effects dominated, and Bloch wall switching begins to emerge as the exchange interaction becomes more prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…We believe this anomaly can largely be attributed to the nature of the microstructure as the films transition from discrete to coalesced grain structures and a possible accompanying transition in domain dynamics. Trunk and co-authors [37] have shown that a transition from Bloch to Neel domain wall structures takes place with decreasing Py film thickness. Neel wall dynamics were found to govern under conditions where demagnetization effects dominated, and Bloch wall switching begins to emerge as the exchange interaction becomes more prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Néel walls have a long and somewhat controversial history (see the discussions in [2,10]), but at present the structure of the Néel wall in very thin films appears to be rather well understood on the basis of micromagnetic arguments [2,9,[11][12][13][14][15][16][17]. The basic features of the predicted one-dimensional Néel wall profiles had been verified experimentally in [18] (see also [19,20]).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its fundamental nature, it has been unclear whether the Néel to Bloch transition at h c is continuous or discontinuous. [12,13,14] A recent and comprehensive magnetostatics study by Kakay and Humphrey [15] indicates that the transition between Néel walls and asymmetric Bloch walls is first order, although the authors were cautious in identifying the specific thickness at which the transition occurs.…”
mentioning
confidence: 99%